Innovative Strategy Implementation of Teaching Materials Assisted Based Culture and Character Nation To Improve Student Learning Outcomes - Kurniah, Nina (Indonesian Journal of Early Childhood Education Studies, 2014)
This study aims to improve student learning outcomes  in Prodi APGPAUD FKIP Bengkulu University through the implementation of innovative strategies namely Contextual Teaching and Learning assisted  teaching materials based on the  culture and character nation. To achieve these objectives done Classroom Action Research  by using a model of Kemmis through four stages of planning, implementation of action, observation and reflection. The subjects were students of PG Paud force in 2013, amounting to 36 people. Data collection techniques used were observation, interviews, and documentation. Research data collected quantitative and qualitative. Quantitative data were analyzed using the statistical t-test while the qualitative data were analyzed an inductively model of "flow analysis". The analysis results showed that the application of the innovative strategies of Contextual Teaching and Learning aided teaching materials based culture and national character, can enhance the learning process associated with the character / attitude (attitude) and learning outcomes related to the mastery of the material significantly. It is influenced by both the lecturer's ability to design and put it into practice, which is owned by the learning potential of students, teaching habits, reinforcement provided by the lecturer, who developed PDA mindset of students, and a conducive learning environment. The advice given is to improve the process and outcomes, especially in college students APGPAUD Prodi, should be designed in a more meaningful learning, is a student center, and supported by teaching materials that integrate the content lectures with various noble character both in design and in its implementation in the classroom.How to citeKurniah, N. (2014). Innovative Strategy Implementation of Teaching Materials Assisted Based Culture and Character Nation To Improve Student Learning Outcomes. Indonesian Journal Of Early Childhood Education Studies, 3(2), 114-117. doi:10.15294/ijeces.v3i2.9484